(untitled) (International Journal of Engineering and Computer Science, 2018)
Resource allocation management in a cloud computing environment is the vital problem. Resource allocation models, QoS, time, conditions of the request for access to services are factors to be focused. Therefore this paper proposes the dynamic resource allocation system which allocates to cloud users. The multi factor technique is applied to optimize the allocation of the virtual machine in cloud computing. In Virtual Machine, while job is allocated and executed in the job scheduler, the first process gets to server and allocates resources. The other remains in waiting state. This refer analyses different virtual machines multi factor such as CPU, Time and Memory usage, Space and Speed. It is used to reduce the job makespan of data processing time and job waiting time, turn out time, to allocate resource efficiently. This system that effectively reducesthe system overload and with multi factors load prediction, the number of physical servers. It achieves better performance in terms of server resource utilization with the response time and minimizes the energy consumption.